An Extreme Programming Approach for Instructor Performance Evaluation System Development - Agung Pambudi; Winda Apriandari (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
The aim of this research was to develop an instructor performance evaluation system for Information Technology Training Center (ITTC) of Islamic State University (UIN) Sunan Kalijaga Yogyakarta using Extreme Programming (XP) methodology. The system was designed to evaluate the performance of instructors in the ICT (Information and Communication Technology) Training process based on certain criteria. The XP method was an agile software development approach that emphasizes iterative development, continuous testing, and customer involvement. The proposed system was developed through several iterations that involve continuous feedback from the ITTC management. The development of the system followed the XP process, which was included planning, designing, coding, testing, refactoring, and integrating. Trainees can access the system to evaluate instructors, and the system helped the ICT training management to determine the instructor's performance for future employment contracts. The system has undergone functionality testing, which resulted in a 100% functionality test and 95,5% of usability test. This system was an effective tool for evaluating the performance of ICT training instructors and can be used to determine the effectiveness of training programs. The system's usability and functionality had been tested and proven to be highly effective, making it a valuable resource for ICT training management.